Raising Bilingual Children in Home Environment of Brunei: A Study on Vocabulary Acquisition - Atiyah Roslan (J-Lalite: Journal of English Studies, 2023)
This study aims to contribute to current research on bilingual children's vocabulary studies and the home environment. It explored how home environments affected children's L1 and L2 vocabulary acquisition. The children in this small-scale study (n=40) were exposed to Brunei Malay (L1) alongside English (L2) from a young age, classifying the children as bilingual first-language learners (BFL). This study examines the children’s L1 and L2 language development and it used vocabulary knowledge as a measuring tool for data analysis. It also considers the home environment and parental role as factors contributing to the children’s language progress. As a result, this study found positive correlations between children's L1 and L2 receptive and active vocabulary knowledge. It also found the children’s L1 and L2 interaction at home with family members. Conversely, the findings shown that there was no significant difference between the responses of 5 and 6 year old children in their L1 and L2 comprehension as well as production tests. This study also found that children who performed well in L1 and L2 vocabulary tests come from households that were open to bilingualism. In addition, parents were open to bilingualism for their children with the condition that the children prioritised their L1 more than L2. The main motive for bilingualism for their children was to enhance their communication skills and increase their chances of future employment. Hence, parents' perception of L1 and L2 is crucial because it shapes the language usages that were exposed to the children at home.